Leading Organizational Learning Harnessing the Power of Knowledge - Marshall Goldsmith, Howard Morgan (John Wiley & Sons, Inc., 2004)

(untitled)
The Leader to Leader Institute has its roots in the social sector and its predecessor, the Peter F. Drucker Foundation for Nonprofit Management, which in January 2003 transferred its ongoing activities to the new identity. The Institute furthers its mission â€œto strengthen the leadership of the social sectorâ€ by providing educational opportunities and resources to leaders. The Institute serves as a broker of intellectual capital, bringing together the finest thought leaders, consultants, and authors in the world with the leaders of social sector voluntary organizations. By providing intellectual resources to leaders in the business, government, and social sectors, and by fostering partnerships across these sectors, the Leader to Leader Institute works to strengthen social sector leaders of the United States and of nations around the globe.